The Code Genie Programming Environment - Jawad, Hadeel Mohammed; de Laski-Smith, Deb; Tout, Samir (IEEE International Conference on Electro Information Technology, 2018)
Computer programming is not easy and many educators and developers have been trying to create a development environment that makes programming easier and more interesting for K12 students. This paper demonstrates one of these efforts by introducing a newly developed educational environment that could help high school students learn computer programming language. Code Genie was designed to integrate art, animation, and code sharing in teaching programming. Using this web-based learning environment, students can learn how to write a program in a JavaScript language, and how to produce artwork from coding, then share it with others. JavaScript was chosen for its popularity, simplicity and because it is a real programming language that is currently used by software developers who create real software products. The Code Genie learning environment and the motivation behind developing it for high school students are discussed in this paper. It was tested during three coding workshops. Student responses to the tool's usefulness and ease of use will be explained.